AB0729 Quality of life assessment in systemic sclerosispatients treated with autologous stem cell transplantation: a longitudinal study. (12th June 2018) - Guimaraes, A.L.C.; Costa-Pereira, K.; Elias, J.B.; Moraes, D.A.; Oliveira-Cardoso, E.A.; Garcia, J.T.; Oliveira, M.C.; Leopoldo, V.; Zombrilli, A.F.; Costa, T.M.; Vasconcelos, M.; Oliveira, M.C.
Abstract : Background: Autologous Hematopoietic Stem Cell Transplantation (AHSCT) has been explored as a therapeutic option for patients with systemic sclerosis (SSc) that do not respond to conventional treatment. Objectives: To investigate changes in quality of life of severe and rapidly progressive SSc patients treated with AHSCT. Methods: This is a longitudinal and comparative study. Patients were evaluated before (n=27), and at 6 (n=27) and 12 months (n=21) after AHSCT. The Generic Questionnaire for Evaluation of Quality of Life Medical Outcomes Study 36 Item Short-Form Health Survey (SF-36) was applied individually, face-to-face, under patient written consent. This questionnaire evaluates eight domains: physical functioning (PF), role-physical (RP), bodily pain (BP), general health (GH), social functioning (SF), vitality (VT), role-emotional (RE) and mental health (MH). Results were transformed into a 0–100 scale, where zero corresponds to a worse health condition and 100 to the best possible score, and submitted to statistical analysis. Significance was defined as p<0.05. Results: Most participants were females (n=24), with mean age of 33 years (standard deviation, SD=10.33) and mean time from diagnosis of 34.4 months (SD=34.89). Before AHSCT, the mostly impaired aspects were: PF (mean=8.33, SD=18.34), and RP (mean=38.52, SD=21.56), while MH (mean=61.63, SD=15.46) and SF (mean=56.87, SD=27.17) were mostly preserved. At 6 and 12 months post-AHSCT, there was significant improvement of the SF-36 scores in the following domains: PF (6 months, p<0.01, 12 months, p<0.01); RP (6 months, p<0.01, 12 months, p<0.01); BP (6 months, p<0.01, 12 months, p<0.01); GH (6 months, p<0.01, 12 months, p=0.02); VT (6 months, p<0.01, 12 months, p<0.01); MH (6 months, p<0.01, 12 months, p<0.01). The SF domain showed significant increase only at 12 months (p=0.02). The only domain in which there was no significant change was RE. Conclusions: Increases in the physical components of quality of life are more evident in the initial periods that follow AHSCT, while improvements in mental state, which are also associated with social aspects, are detected on longer follow-up. These data reinforce the relevance of AHSCT upon patient quality of life, signalling the importance of psychotherapeutic evaluations and follow-up. Disclosure of Interest: None declared